Radiological Mapping of Al-Dabaa Site at Low Depth Profile for Evaluation its Suitability for Disposal of Radioactive Wastes - Badraway, M. (JOURNAL OF ADVANCES IN PHYSICS, 2018)
Disposal sites use series of natural and engineered barriers to contain either radioactive wastes and or spent nuclear fuel. Migration of radionuclide and their pathways studies are carried out as selection criteria of radioactive waste disposal/storage facility. In the framework of the planned NPPs program at Al-Dabaa site, radiological mapping at low depth profile of a specific area within the site has been carried out for evaluation its suitability for disposal of radioactive wastes. Twenty samples were collected from different bore holes of about 12-meterdepthprofile.The samples were transported to the laboratory and prepared for non-destructive assay using well calibrated 60% efficiency High-Purity Germanium (HpGe) detector. The natural radioactivity of 235U, 238U (234Th), 226Ra, 232Th and 40K were determined and quantified. The 235U/238U activity ratios were also calculated and found to be within the natural signature. The Absorbed dose rates (nGy/h) were also calculated and found in the average world value; 59nGy/h. The man-made 137Cs was also found in ultra-low activity concentrations, where the highest value was found to be 0.00987 Bq/kg. The mineralogy of the collected site samples was also investigated by x-ray diffraction (XRD) analysis technique to identify and determine the major mineral structure of the samples. It was observed that Dolomite and Calcite are the major minerals of the investigated site. The results are discussed and represented as histograms, contour mapping and 3D correlations. These results are also going to be used as inputs and bases for a future work; code modeling for evaluation of Al-Dabaa site.